Doing stigma: Online commenting around weight-related news media. (September 2018) - Brooker, Phillip; Barnett, Julie; Vines, John; Lawson, Shaun; Feltwell, Tom; Long, Kiel
Weight stigma results from the mediatisation of 'obesity': conceptually, a medicalised problem resulting from personal bodily irresponsibility. We undertake a frame analysis of 1452 comments on a thematically related online news article published via The Guardian, about the status of 'obesity' as a disability in European Union (EU) employment law. We identify three themes: (1) weight as a lifestyle choice or disability, (2) weight as an irresponsible choice and (3) weight as a simple or complex issue. We contend that the design of the commenting platform prevents counter-narratives from challenging the dominant ('obesity') framing for three reasons: (1) content is driven by comments appearing earlier in the corpus, (2) the commenting system primarily supports argument between polarised rhetorical positions and (3) the platform design discourages users from developing alternative terminologies for producing counter-narratives. In this way, we explore how weight stigma is propagated through online media, and how users' comments intersect with the affordances of the platform itself.